DEVELOPMENT OF KEROPOK LEKOR-TYPE SNACK USING BY-PRODUCTS FROM NILE TILAPIA OREOCHROMIS NILOTICUS: DESENVOLVIMENTO DE UM SNACK DO TIPO KEROPOK LEKOR UTILIZANDO SUBPRODUTOS DA TILÁPIA DO NILO OREOCHROMIS NILOTICUS - Vasconcelos de Andrade , Rildo José; Pinheiro Crasto Amaral, Rodrigo; Carvalho da Silva, Eloá Dandara; Estolano Macedo , Indira Maria; Kazue Sakugawa Shinohara , Neide; Agrelli de Andrade , Humber; Olivera Gálvez , Alfredo; Borda Soares , Roberta; Campagnoli de Oliveira Filho, Paulo Roberto (DESAFIOS - Revista Interdisciplinar da Universidade Federal do Tocantins, 2026)
Keropok lekor is a food product originating from and consumed in Asian countries and may contain MSM in its composition. The present study aimed to develop and carry out physicochemical, nutritional, microbiological, and sensory analyses of keropok lekor using MSM from Nile tilapia byproducts (0, 10, and 20%) and wheat fiber (0, 1, and 2%). Analyses were conducted on color and instrumental texture, pH, lipid oxidation, water activity, total volatile basic nitrogen, proximate composition, microbiological tests, and sensory evaluation. The inclusion of MSM in the keropok´s formulation decreased the redness and yellow, TVB-N, ash, and carbohydrate; it also increased pH, aw, protein, and moisture. The addition of wheat fiber increased the redness, making the product less luminous and with lower TVB-N. Microbiological analyses indicated that the keropok were regulated by the health legislation in Brazil. The sensory analysis showed that the product presented good sensory acceptance with values ranging from “I liked it slightly” to “I liked it moderately”, with no difference between the formulations. Therefore, keropok lekor made with MSM from Nile tilapia and wheat fiber is safe for human consumption and has good sensory acceptance, being a potential food product to be produced on a commercial scale, recommending the inclusion of 2% wheat bran and the addition of 20% tilapia MSM.